NIOSOMAL CARRIER PREPARATION OF PREDNISOLONE FORMULATION AND IN-VITRO EVALUATION - HAJER ABDO,; YASMIN Al-KURDI,; GHADA AL-ASHMOUNY,; FATIMA KUTUB,; EMAN ABDULRHMAN, (International Journal of Pharma and Bio Sciences, 2016)
Niosomes are microscopic lamellar vesicles build from mixture of nonionic surfactant, cholesterol and phosphate buffer with subsequent hydration in aqueous media, capable of entrapping hydrophilic and hydrophobic molecules. The aim of this study is to formulate prednisolone loaded niosomes. Prednisolone is a synthetic corticosteroid commonly used as an anti-inflammatory agent and immunosuppressant. Niosomes are formulated by ether injection method and evaluated for following parameters (a) vesicular diameter (b) Entrapment efficiency (c) in-vitro drug release. Non-ionic surfactants used were span 80 and cholesterol used in 1:2:1 molar ratio. The niosomes prepared were large unilamellar vesicles (LUVS) with higher entrapment efficiency of 69.5 %. The in-vitro diffusion study suggests that higher entrapment efficiency comparatively causes slow release. The results conclusively demonstrates prolongation of drug release at a constant and controlled rate into systematic formulation, have reduced protein–binding, cheap, chemically stable, thus overcoming systemic side effects, reducing administered dose, improving therapeutic efficacy and patient compliance.